The Role of Attention Shifting in Orthographic Competencies: Cross-Sectional Findings from 1st, 3rd, and 8th Grade Students - von Suchodoletz, Antje; Fäsche, Anika; Skuballa, Irene T. (Frontiers in Psychology, 2017)
Attention shifting refers to one core component of executive functions, a set of higher-order cognitive processes that predict different aspects of academic achievement. To date, few studies have investigated the role of attention shifting in orthographic competencies during middle childhood and early adolescence. In the present study, 69 first-grade, 121 third-grade, and 85 eight-grade students’ attention shifting was tested with a computer version of the Dimensional Change Card Sort (DCCS; Zelazo, 2006). General spelling skills and specific writing and spelling strategies were assessed with the Hamburger Writing Test (May, 2002). Results suggested associations between attention shifting and various orthographic competencies that differ across age groups and by sex. Across all age groups, better attention shifting was associated with less errors in applying alphabetical strategies. In third graders, better attention shifting was furthermore related to better general spelling skills and less errors in using orthographical strategies. In this age group, associations did not differ by sex. Among first graders, attention shifting was negatively related to general spelling skills, but only for boys. In contrast, attention shifting was positively related to general spelling skills in eighth graders, but only for girls. Finally, better attention shifting was associated with less case-related errors in eight graders, independent of students’ sex. In sum, the data provide insight into both variability and consistency in the pattern of relations between attention shifting and various orthographic competencies among elementary and middle school students.